Mitochondrial Transcription of Entomopathogenic Fungi Reveals Evolutionary Aspects of Mitogenomes - Varassas, Stylianos P.; Kouvelis, Vassili N. (Frontiers in Microbiology, 2022)
Entomopathogenic fungi and more specifically genera Beauveria and Metarhizium have been exploited for the biological control of pests. Genome analyses are important to understand better their mode of action and thus, improve their efficacy against their hosts. Until now, the sequences of their mitochondrial genomes were studied, but not at the level of transcription. Except of yeasts and Neurospora crassa, whose mt gene transcription is well described, in all other Ascomycota, i.e., Pezizomycotina, related information is extremely scarce. In this work, mt transcription and key enzymes of this function were studied. RT-PCR experiments and Northern hybridizations reveal the transcriptional map of the mt genomes of B. bassiana and M. brunneum species. The mt genes are transcribed in six main transcripts and undergo post-transcriptional modifications to create single gene transcripts. Promoters were determined in both mt genomes with a comparative in silico analysis, including all known information from other fungal mt genomes. The promoter consensus sequence is 5’-ATAGTTATTAT-3’ which is in accordance with the definition of the polycistronic transcripts determined with the experiments described above. Moreover, 5’-RACE experiments in the case of premature polycistronic transcript nad1-nad4-atp8-atp6 revealed the 5’ end of the RNA transcript immediately after the in silico determined promoter, as also found in other fungal species. Since several conserved elements were retrieved from these analyses compared to the already known data from yeasts and N. crassa, the phylogenetic analyses of mt RNA polymerase (Rpo41) and its transcriptional factor (Mtf1) were performed in order to define their evolution. As expected, it was found that fungal Rpo41 originate from the respective polymerase of T7/T3 phages, while the ancestor of Mtf1 is of alpha-proteobacterial origin. Therefore, this study presents insights about the fidelity of the mt single-subunit phage-like RNA polymerase during transcription, since the correct identification of mt promoters from Rpo41 requires an ortholog to bacterial sigma factor, i.e. Mtf1. Thus, a previously proposed hypothesis of a phage infected alpha-proteobacterium as the endosymbiotic progenitor of mitochondrion is confirmed in this study and further upgraded by the co-evolution of the bacterial (Mtf1) and viral (Rpo41) originated components in one functional unit.